TINDAK LANJUT TERHADAP PENERAPAN ELEKTRONIK VOTING DALAM PELAKSANAAN PEMILIHAN KEPALA DAERAH BERDASARKAN PERATURAN PERUNDANG-UNDANGAN - Beni Willia Saputra; Bahder Johan Nasution (Universitas Jambi, Fakultas Hukum, 2021)
The thesis focuses on determining the application of Electronic Voting used for the General Election of Regional Heads in Indonesia. Electronic Voting is a system that utilizes electronic devices and processes digital information to create ballots, cast votes, calculate vote acquisitions, display vote acquisitions and maintain and generate audit trails. E-voting is considered to be applied for utilization on the scale of General Elections to Regions that one may achieve election effectiveness and efficiency. Aside from that, it can decrease costs of realization, shorten the voting time to the vote-counting process, and certain other advantages obtained from the realization of Electronic Voting. The problem of this research is how to follow up the juridical regulation on the realization of e-voting in the utilization of Regional Head Election based on the laws and regulations in Indonesia, furthermore find out the legal problems of implementing e-voting in the Regional Head Election in Indonesia. The type of research used is normative juridical, namely legal research methods execute by examining library materials or secondary materials. The previous section has broadly described that there is a vacuum of Electronic Voting system in the application of the General Election to the Regions. After all, there is no KPU regulation whichever would be used as the basis for applying this Electronic Voting system, as much as this system demand to be reviewed It be implemented yet because there are deficiencies in the application of the Electronic Voting System process that would eventually fail the implementation.